Medieval Worlds: A Sourcebook - Anderson, Roberta; Bellenger, Dominic Aidan (London Routledge, 2003)
Complete with introductions, full commentary, glossary, and a guide to further reading, Medieval Worlds is a comprehensive sourcebook for the study of Western Europe from the fifth to the fifteenth century.Drawing on a wide range of documents, from chronicles, legal, state, and church documents, to biographies, poems, and letters from all over Europe, the authors expertly illustrate to the reader the unity and complexity of the medieval world.Amongst many more, central issues discussed include: the diverse world of monasteries the Papacy the Crusades women the roles of the town and countryside.Medieval Worlds presents the reader with a view of the medieval era as it was: one of immense diversity with openness to new ideas, and outreach in areas from technology to natural philosophy.
Keywords: Middle Ages (500-1400); History; Europe